DESIGN INFORMATION SYSTEM PCB (PRINTED CIRCUIT BOARD) PT. SUKMA BETA SEMPURNA BEKASI - Sugito Sugito; Aqwam Rosadi Kardian, Skom.,MM. (Jurnal Sistem Informasi, 1998)
The rapid progress of technology development it will bring positive impact to otherparts, like the case above shows a package system can give more meaning to that use,because the package design system or the new system can reduce the nature of worktime or still less efficient manually.